Compliance and treatment satisfaction of post menopausal women treated for osteoporosis. Compliance with osteoporosis treatment - Huas Dominique; Debiais Françoise; Blotman Francis; Cortet Bernard; Mercier Florence; Rousseaux Chantal; Berger Véronique; Gaudin Anne-Françoise; Cotté François-Emery (BMC, 2010)
Abstract Background Adherence to anti-osteoporosis treatments is poor, exposing treated women to increased fracture risk. Determinants of poor adherence are poorly understood. The study aims to determine physician- and patient- rated treatment compliance with osteoporosis treatments and to evaluate factors influencing compliance. Methods This was an observational, cross-sectional pharmacoepidemiological study with a randomly-selected sample of 420 GPs, 154 rheumatologists and 110 gynaecologists practicing in France. Investigators included post-menopausal women with a diagnosis of osteoporosis and a treatment initiated in the previous six months. Investigators completed a questionnaire on clinical features, treatments and medical history, and on patient compliance. Patients completed a questionnaire on sociodemographic features, lifestyle, attitudes and knowledge about osteoporosis, treatment compliance, treatment satisfaction and quality of life. Treatment compliance was evaluated with the Morisky Medication-taking Adherence Scale. Variables collected in the questionnaires were evaluated for association with compliance using multivariate logistic regression analysis. Results 785 women were evaluated. Physicians considered 95.4% of the sample to be compliant, but only 65.5% of women considered themselves compliant. The correlation between patient and physician perceptions of compliance was low (κ: 0.11 [95% CI: 0.06 to 0.16]). Patient-rated compliance was highest for monthly bisphosphonates (79.7%) and lowest for hormone substitution therapy (50.0%). Six variables were associated with compliance: treatment administration frequency, perceptions of long-term treatment acceptability, perceptions of health consequences of osteoporosis, perceptions of knowledge about osteoporosis, exercise and mental quality of life. Conclusion Compliance to anti-osteoporosis treatments is poor. Reduction of dosing regimen frequency and patient education may be useful ways of improving compliance.